METABOLIC CHARACTERISTICS OF GASTRIC CONTENTS UNDER CONDITIONS OF NEUROMUSCULAR DYSFUNCTION OF THE ESOPHAGOGASTRIC JUNCTION - A.M. Halinska; O.V. SEVERYNOVSKA; O.O. HALINSKYI (Biotechnologia Acta)
Neuromuscular dysregulation at the esophagogastric junction, characteristic of achalasia cardia, leads to alterations in the metabolic composition of gastric contents, particularly in acidity, pepsin concentration, bile acids, and protective mucosal factors. Investigating these changes is essential for understanding the pathophysiological mechanisms underlying motor-secretory dysfunction and the development of esophageal and gastric disorders. The relevance of such research is underscored by the limited available data on the biochemical composition of gastric juice in the context of esophageal dysfunction, especially achalasia cardia, thereby highlighting the need for further investigations in this area.